Effects of acid rain on geotechnical properties of tropical residual soils - Bakhshipour, Zeinab (2017)
Acidic deposit that falls to earth from the atmosphere is named acid rain. Sulfur dioxide (SO2) and oxide of nitrogen (NOx) are being constantly released as gases into the atmosphere. These oxides react with the rainwater to produce stronger acids and might lower the pH to 4.5 or even 2.0. This research aimed at determining the effect of acid rain on residual soil and kaolinite in the tropical area. Fore types of soils sedimentary residual soil (SRS), igneous residual soil (IRS), primary kaolinite (PK) and secondary kaolinite (SK) with different properties were chosen. Soaking and infiltration methods were employed to simulate the natural environment and reaction of acid rain on the selected soils based on short-term and long-term reaction. For the soaking method, the specimens were kept in the artificial acid rain (AAR) container for 7, 14, 28, and consequently 90 days, while in the infiltration method, the specimens were kept at flux of AAR for 1, 5, 10, and 20 years at different pH levels for both methods. The AAR was prepared by adding certain volume of 0.005M nitric acid (HNO3) and sulfuric acid (H2SO4) to the deionized distilled water. The pH values of the AAR were adjusted to 2, 3, 4, 5, and 5.6. All soils’ properties via physico-chemical and mechanical were assessed before and after treatment of specimens with AAR to identify the effect of the AAR on the soils. For the mechanical properties tests, unconfined compressive strength (UCS), consistency limits, optimum moisture content (OMC), maximum dry density (MDD), hydraulic conductivity, and onedimensional consolidation tests were carried out. Whereas, to examine the effects of AAR on soil chemical mechanism, the microstructural tests were performed using zeta potential (ζ), Atomic adsorption spectroscopy (AAS), X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FTIR), scanning electron microscope (SEM), and energy dispersive X-ray spectroscopy (EDX). In soaking method (i.e. short-term), low pH value of AAR changed the characterization of SRS IRS, PK, and SK, and led to an increase in soil strength and maximum dry density (MDD), and reduction in the hydraulic conductivity, Atterberg limits, and optimum moisture content (OMC). In terms of long-term effect of acid rain, the low pH value and high fluxes of AAR changed the characterization of SRS IRS, PK, and SK and led to a reduction in soil strength and MDD, and an increase in the hydraulic conductivity, Atterberg limits, and OMC, initial void ratio, and Cc of SRS, IRS, PK, and SK. Longterm flux of AAR led to a further increase in compressibility of the studied soils. Regarding the influence of flux of acid rain on the soil properties, the acidic pH level of rain has significant effects on the physico-chemical properties. The effect of acid rain on the properties of soils will become more serious if the rainwater is further acidified due to heavier industrialization.